Bioprospecting of microorganism-based industrial molecules - Singh, Sudhir P.; Upadhyay, Santosh Kumar (Wiley, 2022)
"Bioprospecting of Microorganism based Industrial Molecules demonstrates biomass value of neutraceutical, pharmaceutical, food, biomedical, bioenergetic importance. This book covers diverse aspects of bioprospecting of microorganisms for the extraction of several industrially important biomolecules. The authors present an amalgamation of translational research on bioresource utilization and ecological sustainability that will further the reader's knowledge of the applications of different microbial diversity and reveal new avenues of research investigation. Readers will also benefit from: * A thorough introduction to microbial biodiversity and bioprospecting * An exploration of anti-ageing and skin lightening microbial products and microbial production of anti-cancerous biomolecules * A treatment of UV protective compounds from algal biodiversity and polysaccharides from marine microalgal sources * Discussions of microbial sources of insect toxic proteins and the role of microbes in bio-surfactants production Perfect for academics, scientists, researchers, graduate and post-graduate students working and studying in the areas of microbiology, food biotechnology, industrial microbiology, plant biotechnology, and microbial biotechnology, Bioprospecting of Microorganism based Industrial Molecules is an indispensable guide for anyone looking for a comprehensive overview of the subject"-- Provided by publisher.